Meaning of Success: perception of medical students, and faculty-A Qualitative Study from a medical school in Mauritius (Nepal Journal of Epidemiology, 2020)
Background: The objective of this study was to find what undergraduate medical students and teaching faculty perceive success to be.Methods: A descriptive phenomenological qualitative study was designed and conducted on faculty and medical students at Sir Seewoosagur Ramgoolam Medical College, Mauritius. NVivo 12 (Windows) Plus software was implemented for data analysis and thematic analysis was performed.Results: The codes/nodes namely being: Satisfaction, Accomplishment, Actions, Motivations, Extrinsic Factors and Intrinsic Factors were identified in the transcribed data. Satisfaction was described as the positive emotions and notions intimately related as well as synonymously associated with success. Accomplishment as the attainment and fulfilment of any physical, mental, emotional, social, occupational, personal goal or desire by an individual. Actions was the arsenal of physical processes, acts of planning, goal setting or forethinking exercised by the individual. Motivations was the drive to attain the preset goal or notion be it positive or negative, applies to factors that enable a subject to strive forwards. Extrinsic Factors were the external determinants and definition of success perceived by the subject. Intrinsic Factors were the subject’s internal organic, comprehension and definition of success. The themes generated were: Products of Success, Mechanisms of Success and Concepts of success.Conclusion: A tangible demarcation is noticeable between the preconceived general impression of success and the vast multifactorial cohort of intrinsic and extrinsic factors coupled to the highly emotional aspects which were brought forth.